2018
DOI: 10.1080/15348431.2018.1499512
|View full text |Cite
|
Sign up to set email alerts
|

Community-driven leadership: Mexican-origin farmworking mothers resisting deficit practices by a school board in California

Abstract: We examine how the community-driven leadership (CDL) of farmworker mothers challenged deficit practices of the local school board, which decided to close the school in the community. CDL is the ability of mothers to activate their community cultural wealth to mobilize their resources in search of better educational opportunities. The mothers organized to take action in order to disrupt systems of oppression embedded in their local public school system. Testimonios showcase the inequalities the mothers experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 52 publications
(46 reference statements)
0
9
0
Order By: Relevance
“…Together, these six forms of capital represent the cultural assets and knowledge of communities of Color, and their capacity to thrive despite institutional barriers. Research informed by a CCW framework empowers and affirms the cultural wealth and resources of muxeres, while attributing social inequities to structural factors instead of cultural differences framed as deficits (Aragon, 2018; Deeb‐Sossa & Manzo, 2020; Guzmán et al, 2018).…”
Section: A Community Cultural Wealth (Ccw) Frameworkmentioning
confidence: 99%
“…Together, these six forms of capital represent the cultural assets and knowledge of communities of Color, and their capacity to thrive despite institutional barriers. Research informed by a CCW framework empowers and affirms the cultural wealth and resources of muxeres, while attributing social inequities to structural factors instead of cultural differences framed as deficits (Aragon, 2018; Deeb‐Sossa & Manzo, 2020; Guzmán et al, 2018).…”
Section: A Community Cultural Wealth (Ccw) Frameworkmentioning
confidence: 99%
“…Finnigan and Lavner (2012), for instance, described how a district came to close a school, even though officials left open five other schools that, according to their own closure criteria, they had ranked as more deserving of closure. In California, district administrators decided to close a school due to budget "deficits," yet they built a new school in a wealthier neighborhood in the same district (Deeb-Sossa & Manzo, 2018;Deeb-Sossa & Moreno, 2016). And, in Richmond, Virginia, officials closed a school that was both more cost efficient and stronger academically than other schools that remained open (Siegel-Hawley et al, 2017).…”
Section: Implementation Of Closurementioning
confidence: 99%
“…Some longitudinal research documented an increase in student absenteeism across locales (Engberg et al, 2012;Larsen, 2014), though Engberg et al (2012 found that the attendance effect faded over time. Both qualitative and quantitative studies indicate that urban and rural students affected by closure could experience longer bus rides, increased travel time, more limited school accessibility, and reduced safety; these effects were particularly pronounced for poor students and students of color (Conner & Cosner, 2014;Deeb-Sossa & Manzo, 2018;de la Torre et al, 2015;Graham et al, 2014;Hyndman et al, 2010;Killeen & Sipple, 2000;Lee & Lubienski, 2016: Spence, 1998. Perhaps it is not surprising, then, that closure diminished extracurricular participation (Graham et al, 2014;, even though, in some rural places, the number of available extracurricular opportunities expanded (Alsbury & Shaw, 2005;Hyndman et al, 2010).…”
Section: Impacts Of Closurementioning
confidence: 99%
“…While this is certainly a challenge, some scholarship reviewed here has THE COUNTER-DEFICIT LENS successfully researched across the ideology-structure divide (e.g. Casapulla and Hess, 2017;Deeb-Sossa and Manzo, 2018;Monzó, 2016;Shapiro, 2019). These findings suggest important implications for research and educators who seek to improve the educational experiences of marginalized youth.…”
Section: Discussionmentioning
confidence: 99%
“…Other researchers have urged teachers to build cultural solidarity to improve math performance (Miles et al, 2019). Ultimately, leveraging students' or families' cultural wealth and funds of knowledge toward success on reading tests (M. , toward college readiness (Jayakumar et al, 2013), and toward engagement and 21st-century skills like digital literacy (Beane-Folkes & Ellison, 2018), or toward leaving the public education system for charter schools (Deeb-Sossa & Manzo, 2018) will not undo systems of injustice. When cultural assets are leveraged for individual uplift, the broader goal of social justice for marginalized communities can become obscured.…”
Section: Challenging Ideology and Accepting Structuresmentioning
confidence: 99%